Rational design of zero-dimensional manganese(II) halide hybrids with suppressed melting temperatures - Singh, Shivangi; Marayathungal, Jumana Hasin; Das, Deep Kumar; Khan, Akram Aadil; Bakthavatsalam, Rangarajan; Hathwar, Venkatesha R.; Kundu, Janardan (JOURNAL OF PHYSICAL CHEMISTRY C, 2024)
Keywords: ORGANIC-INORGANIC PEROVSKITES; TRANSITION

Supercooled liquid phases of luminescent zero dimensional metal halide hybrids - Kumar Das, Deep; Marayathungal, Jumana Hasin; Palakkolil, Athira; Sarma, Dhritismita; Khan, Akram Aadil; Kumar, M. Praveen; Kudlu, Ashwath; Choudhary, Mahendra; Hathwar, Venkatesha R.; Pujala, Ravi Kumar; Mahata, Arup; Kundu, Janardan (Journal of Physical Chemistry Letters, 2025)
Chemical design of metal halide hybrids (MHHs) with suppressed melting point (T-m) allows access to glassy phases from their liquid-melts. Thermal phase change (crystal-melt-glass) properties of glassy MHHs (with glass transition temperature T-g > room temperature) have been exploited for device applications. However, room temperature stable supercooled liquid (SCL) MHHs (with T-g < room temperature), originating from glass-SCL phase change, remain inaccessible. Here, a molecular design strategy is reported to access ambient stable, melt-processable, SCL multimetallic bromide hybrids (Mn2+,Cd2+; Mn2+,Zn2+; Benzyltributylammonium) with low T-g (15-16 degrees C), low T-m (90-100 degrees C), green luminescence, and high optical transparency. Structural, optical, thermal, and computational analyses highlight chemical design principles and support dopant (Mn2+) based luminescence. Rheological measurements confirm the SCL phase that shows thermal hysteresis and estimate relaxation time scales. This work provides a new material platform showcasing enhanced melt-processability for fabrication of moldable devices, unravelling chemical makeup-property correlation and expanding the material phase types of MHHs.